Influence of psychosocial factors on the effectiveness of infertility treatments - Pereira,Beatriz Sá (2020)
Abstract Overview and Aims: Infertility is a rising problem in our society, with an increasing prevalence in the past years, resulting of an interaction of multifactorial causes, with great demand and personal suffering, being imperative to adopt an integrated view where physiology is intimately related to social and psychological processes. This study aims to identify the factors that contribute to the effectiveness of infertility treatments and overall outcomes of pregnancy and birth, with a special focus on the psychosocial component. Study Design and Population: This is a retrospective, descriptive and causal study of 278 infertile couples followed from 2015 to 2018. Methods: Data was collected on the causes of infertility, the treatments performed, and their effectiveness. The aim was to cross these data with clinically relevant psychological symptoms, through Brief Symptom Inventory (BSI) and Fertility’s Problem Inventory (FPI), in order to assess the stress inherent to their condition. Results: Emotional disorders are significantly more prevalent in women (p<0.05), as well as social and sexual concerns. The Need for parenthood and the Rejection of childfree lifestyle are the problems that most concern both elements of the couple. Conclusions: It was found that the couple's psychosocial component has an influence on the infertility’s treatment process, with an impact on its outcome. Symptoms such as Depression, Hostility and Phobic anxiety were higher in women who did not become pregnant after the treatment, as well as in men. Results were even more enlightening regarding pregnancy. For women, somatization is related to abortion (p<0.05), as well as most symptoms of BSI; whereas for men, sexual and relationship concerns are associated with male etiology and less likelihood to give birth.